Attitude toward aloneness and ability to be alone in middle and late childhood - E Galanaki (ΣΚΕΨΥ - Σύγχρονη Κοινωνία, Εκπαίδευση και Ψυχική Υγεία, 2012)
Although the painful experience of loneliness has been largely investigated, attitude toward aloneness and ability to be alone during middle and late childhood remains a highly neglected research issue. The Ability to Be Alone Questionnaire (Berlin, 1990), and the Aversion to Aloneness and Affinity for Aloneness subscales of the Loneliness and Aloneness Scale for Children and Adolescents (Marcoen & Goossens, 1993) were used with 136 fourth and sixth graders (Study 1); also, a sentence completion task assessing feelings about aloneness (Coleman, 1974), and three questions assessing the ability to differentiate between aloneness and loneliness (Galanaki, 2004) (Study 2) were used with 108 fourth and sixth graders. All participants came from primary schools of Athens, Greece. Results showed a decrease from middle to late childhood in children’s aversion to aloneness, and an increase in their capacity to understand that loneliness may be experienced even in the presence of others. Ability to be alone and affinity for aloneness did not show any statistically significant increase with age. The majority of fourth graders were able to understand that “alone” does not necessarily means “lonely”, but had difficulties in accepting the state “feeling lonely even in the presence of others”. Empirical support for an ambivalent attitude toward aloneness during both these age periods also emerged. Gender differences were not found. Findings are discussed in the framework of the existing research on children’s understanding and experience of aloneness and solitude, and suggestions for future research are made.